Analysis of Advertising Effectiveness on Television Using the Epic Model - Kanzha Alif Pasha; Wahyunengsih W (Madani: Jurnal Ilmiah Multidisiplin, 2023)
As a condition that occurs continuously in the course of life, the trading system has evolved in such a way that it has reached the digital trading system practiced by today's society. Over time, advertising in digital media is considered more effective than mainstream media such as television advertisements. Supported by statistical data collection techniques that make it easier for the audience to detect and display social media ads, or can directly target potential buyers who have conducted similar searches in the past. However, several facts still show that TV advertising is still the top choice by brands and has the highest percentage of ad spending compared to other advertisements. This quantitative study took primary data through questionnaires and the results of the data were processed using SPSS 25 to test the effectiveness of TV advertising with non-parametric tests and ANOVA tests.